Foam layered apparatus with foam stabilization - Liaposhchenko, А.; Khukhryanskiy, О.; Moiseev, V.; Manoilo, Е. (Lviv Polytechnic National University, 2019)
In work were studied the expanded models of foaming apparatuses with gratings, made of tubes of different diameters. The questions of intensification of foam devices with the use of coarsegrating lattices are considered. The possibility of deep cleaning and practically complete cleaning of gases from ammonia and fluoride compounds with their separate absorption is noted.
Keywords: industrial gas emissions; cleaning process; hydrodynamics; mass transfer; foam apparatus; foam layer; research of purification processes; stabilization of foam layer; intensive apparatus